Solve the system by substitution.

minus, 5, x, plus, 3, y, equals, 2
−5x+3y=
2
y, equals, 2, x
y=
2x

1 answer

We can substitute the expression "2x" for "y" in the equation -5x + 3y = 2:

-5x + 3(2x) = 2
-5x + 6x = 2
x = 2

Now that we have solved for x, we can find the value of y by substituting x = 2 back into y = 2x:

y = 2(2)
y = 4

Therefore, the solution to the system of equations is x = 2 and y = 4.
Similar Questions
  1. Solve the system by substitution.y, equals, minus, 6, x y= −6x y, equals, minus, 4, x, plus, 4 y= −4x+4 Answer Attempt 1 out
    1. answers icon 1 answer
  2. Solve the system by substitution.minus, 2, y, minus, 10, equals, x −2y−10= x minus, 10, x, minus, y, equals, minus, 14
    1. answers icon 1 answer
  3. Solve the system by substitution.minus, 8, x, minus, 7, y, equals, minus, 5 −8x−7y= −5 minus, x, equals, y −x= y
    1. answers icon 1 answer
  4. Solve the system by substitution.minus, 5, x, minus, 9, y, equals, 33 −5x−9y= 33 minus, y, minus, 1, equals, x −y−1= x
    1. answers icon 1 answer
more similar questions